Agricultural dust explosions in 2005 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 13 dust explosions reported in the U.S. in 2005 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 6 in 2004 and a ten-year average of 10.5 explosions.
Keywords: Grain dust; Dust explosions